Selective ultrasensitive FBG-SBL chemosensor for detection of copper ions in water resources based on plasmon resonance energy transfer. (September 2022) - Samavati, Zahra; Samavati, Alireza; Fauzi Ismail, Ahmad; Sohaimi Abdullah, Mohd; Hafiz Dzarfan Othman, Mohd
Graphical abstract: Highlights: SBL/Au decorated FBG sensor for conscious and selective detection of Cu 2+ . Interaction of the SBL as anionic chelates with Cu 2+ changes the SPR condition. Linear dynamic range, excellent repeatability and low LOD (<WHO standard). FBG-SBL chemosensor is suitable for online and remote monitoring of water resources. Abstract: In this study, the gold (Au) coated fiber Bragg grating (FBG) probe decorated with Schiff base ligands (SBL) with variable denticity is proposed as a susceptible sensor for monitoring the copper ions (Cu 2+ ) concentration in an aqueous solution. The sensing principle can be attributed to the interaction of the SBL coated on Au/FBG, which serves as anionic chelates with Cu 2+, altering the environment refractive index and changing the surface plasmon resonance (SPR) condition. The sensitivity and limit of detection (LOD) through a Bragg wavelength shift are measured to be 23.1 pm/µM and 0.07 µM respectively, with a dynamic range of up to 4  µM (µM, 2.5 ppm), which is within the acceptable limit specified by the World Health Organization (WHO) for safe drinking water (1.3 ppm). The probe shows an assertive coordination behaviour towards Cu 2+ for selective detection compared to other heavy metals. Excellent reusability (6 trial times) and specificity and portability make FBG-SBL chemosensor suitable for online monitoring of water resources.